Long-term iron supplementation combined with vitamin B6 enhances maximal oxygen uptake and promotes skeletal muscle-specific mitochondrial biogenesis in rats - Zhou, Lei; Mozaffaritabar, Soroosh; Kolonics, Attila; Kawamura, Takuji; Koike, Atsuko; Kéringer, Johanna; Gu, Yaodong; Karabanov, Roman; Radák, Zsolt (Frontiers in Nutrition, 2024)
Iron is an essential micronutrient that plays a crucial role in various biological processes. Previous studies have shown that iron supplementation is related to exercise performance and endurance capacity improvements. However, the underlying mechanisms responsible for these effects are not well understood. Recent studies have suggested the beneficial impact of iron supplementation on mitochondrial function and its ability to rescue mitochondrial function under adverse stress in vitro and rodents. Based on current knowledge, our study aimed to investigate whether the changes in exercise performance resulting from iron supplementation are associated with its effect on mitochondrial function. In this study, we orally administered an iron-based supplement to rats for 30 consecutive days at a dosage of 0.66 mg iron/kg body weight and vitamin B6 at a dosage of 0.46 mg/kg. Our findings reveal that long-term iron supplementation, in combination with vitamin B6, led to less body weight gained and increased VO2 max in rats. Besides, the treatment substantially increased Complex I- and Complex II-driven ATP production in intact mitochondria isolated from gastrocnemius and cerebellum. However, the treatment did not change basal and succinate-induced ROS production in mitochondria from the cerebellum and skeletal muscle. Furthermore, the iron intervention significantly upregulated several skeletal muscle mitochondrial biogenesis and metabolism-related biomarkers, including PGC-1α, SIRT1, NRF-2, SDHA, HSL, MTOR, and LON-P. However, it did not affect the muscular protein expression of SIRT3, FNDC5, LDH, FIS1, MFN1, eNOS, and nNOS. Interestingly, the iron intervention did not exert similar effects on the hippocampus of rats. In conclusion, our study demonstrates that long-term iron supplementation, in combination with vitamin B6, increases VO2 max, possibly through its positive role in regulating skeletal muscle-specific mitochondrial biogenesis and energy production in rats.